An investigation into the adoption of ICT governance practices and software development processes in the state of Sergipe - Silva, Claudio Junior N.; Nogueira, Toniclay; do Nascimento, Rogério Patrício Chagas; Colaço Júnior, Methanias (iSys - Journal of Information Systems, 2020)
In a continuously competitive market, companies are increasingly relying on computerized systems to reduce costs and increase their productivity. A flaw in mapping or defining software development processes can pose serious risks to organizations, which have come to recognize the importance of technology for the business. As a result, companies started to adopt practices and methodologies to manage ICT services and the software development process. The objective of this work was to present the results of a survey conducted with 52 ICT managers from companies in the state of Sergipe to investigate the adoption of ICT governance practices and software development processes in these companies. The product of this study is a record of the panorama of the adoption of governance practices and the use of software development processes by Sergipe companies. It was observed that 19.2% of respondents indicated that the companies in which they work fully adopt the software development process to meet the needs of the organization and that they use at least one practice of ICT governance. Among the most used practices in organizations, 63% reported using ITIL and 56% used their own or customized ICT Strategic Planning (ICT TIP). In just 23% of organizations, major business processes were fully supported by computerized systems. It is expected that such research will provide information that portrays the reality of the use of ICT governance practices and software development processes of Sergipe companies and that can guide managers in the use and adoption of best practices that allow the alignment of the objectives of ICT and business.